Answer:
x = 10
Step-by-step explanation:
-8(-3 + x) = -56
Distribute the -8 into the (-3 + x).
24 - 8x = -56
Subtract 24 from both sides.
-8x = -80
Divide both sides by -8.
x = 10.
Proof:
-8(-3 + x) = -56
Substitute variable.
-8(-3 + 10) = -56
Add inside parenthesis.
-8(7) = -56
Multiply.
-56 = -56
The magnitude of WX is
⇒ c
Step-by-step explanation:
The magnitude of XY (its length) where,
is IXYI =
∵ W = (-2 , 8 , -3)
∵ X = (1 , 4 , -1)
- To find the magnitude of WX use the formula above
∴
= -2 and
= 1
∴
= 8 and
= 4
∴
= -3 and
= -1
- Substitute these values in the rule above
∵ IWXI =
∴ IWXI =
The magnitude of WX is
Learn more:
You can learn more about the position of an object in brainly.com/question/10940255
#LearnwithBrainly
Answer:
A.non at all so, please choose the right answer